Rescuing the (Open) Theistic Multiverse Against Two Recent Challenges - Lougheed, Kirk (Sophia, 2025)
One theistic account of creation says that God created the best possible world in the form of a multiverse containing all and only all of the universes sufficiently good enough to create. Certain proponents of this view urge that it solves the problem of no best world and need not commit one to affirming divine middle knowledge. We address two recent challenges to the (open) theistic multiverse. First, Marshall Naylor argues that what he calls the Cantorian account of divine creation is better than any theistic multiverse account because it provides more satisfying answers to a number of philosophical problems (2020). Second, Elliot Crozat criticizes the open theistic multiverse by arguing that if God lacks middle knowledge, God cannot know infallibly that the universe token he creates will be the right type (i.e., sufficiently good enough for inclusion in the multiverse) (2019). We show that Naylor’s alternative violates incredibly strong moral intuitions and that Crozat’s objection fails to appreciate that on open theism God still knows all the possible future outcomes. Theistic multiverse accounts of divine creation in general, and one cojoined with open theism in particular, remain unscathed in the face of the criticisms offered by Naylor and Crozat.